2007
DOI: 10.1161/hypertensionaha.106.070565
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Type 1 Receptor Gene Regulation

Abstract: A ngiotensin II (Ang II), the major bioactive peptide of the renin-angiotensin system, was originally described as a potent vasoconstrictor. It is now recognized as a multifunctional hormone influencing many cellular processes, including cell growth, apoptosis, migration, inflammation, and fibrosis. 1,2 Under pathological conditions, the vasoconstrictor, mitogenic, proinflammatory, and profibrotic actions of Ang II contribute to altered vascular tone, structural remodeling, and endothelial dysfunction. [3][4][… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 116 publications
(148 reference statements)
0
10
0
Order By: Relevance
“…Cell surface expression of AT1R is regulated by receptor internalization and this is modulated by multiple proteins including arrestins and ATRAP (4). Transcriptional regulators of AT1R gene include glucocorticoids and interleukin 1β (5). Posttranscriptional regulation of the AT1R mRNA transcript has been established to be an important regulatory mechanism of AT1R expression by insulin, statins and estrogen (6–11).…”
Section: Introductionmentioning
confidence: 99%
“…Cell surface expression of AT1R is regulated by receptor internalization and this is modulated by multiple proteins including arrestins and ATRAP (4). Transcriptional regulators of AT1R gene include glucocorticoids and interleukin 1β (5). Posttranscriptional regulation of the AT1R mRNA transcript has been established to be an important regulatory mechanism of AT1R expression by insulin, statins and estrogen (6–11).…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies have shown that a wide range of physiological and pathological stimuli modulate AT 1 R expression in a number of cell types and tissues (40). We first demonstrated that ATP induces down-regulation of AT 1 R signaling in rat cardiac fibroblasts.…”
Section: Discussionmentioning
confidence: 89%
“…The AT1R overexpression studies discussed in the preceding paragraph each utilized AT1 A R, which may reflect the endogenous response to AT1R ligand stimulation, but leaves the effect of tissue-specific AT1R subtype expression on EGFR transactivation unexplored. Additionally, AT1R subtype expression may not necessarily depend solely on the tissue type, but could be influenced by pathophysiologic conditions or developmental stage [68], thereby impacting EGFR transactivation. Indeed, studies using rat cardiac fibroblasts at distinct stages of development have reported different abilities of AT1R to mediate EGFR transactivation.…”
Section: At1r-mediated Egf Receptor Transactivationmentioning
confidence: 99%